Exploring the risk factors associated with youth offending behavior in Cape Town - Mohajana, Lintle (2013)
Includes bibliographical references.The study explored the risk factors associated with youth offending behaviour in Cape Town, in order to suggest, from a social development point of view, preventive measures that address the risk factors from an outset. The sample that was used consisted of twenty reforming youth offenders (fifteen males and five females) at REALISTIC, a youth restorative centre in Cape Town. The study adopted a qualitative, exploratory approach, using a semi-structured interview schedule for face to face interviews. The sample was purposive and based on the selection of the administrators of the organisation. The results of the interviews, compared with relevant literature and theoretical framework, led to the findings of the study. The findings revealed that substance abuse, academic failure, anti-social peers, low socio-economic status in families and disorganized communities influence offending behaviour among the youth. Additionally, the absence of primary care givers and institutional failures on basic services delivery also exacerbate youth offending behaviour